Saudi Arabia : Tackling Emerging Economic Challenges to Sustain Strong Growth - Al-Darwish, Ahmed (Departmental Papers; Departmental Paper ;, 2015)
Saudi Arabia: Tackling Emerging Economic Challenges to Sustain Strong Growth.